DESIGN AND DEVELOPMENT OF IN-GAME CURRENCY E-MARKETPLACE USING LARAVEL FRAMEWORK WITH EXTREME PROGRAMMING METHOD - Daniel Apdianto Herman; Andy Kho (Universitas Internasional Batam, 2022)
In-game currency can be used to purchase various in-game items, especially in online games. In addition, in-game currency is also widely traded by players in certain online games. This eventually causes the potential for scam in buying and selling in-game currency to increase. This happened because there is no place that can be used by players to do transactions safely. The purpose of this research is to design and develop an e-marketplace for in-game currency using the Extreme Programming method which consists of planning, design, coding, and testing stages. This in-game currency e-marketplace application will be developed using the Laravel framework, which is one of the open-source PHP frameworks. The result of this research is an e-marketplace application that can be used by in-game currency buyers or sellers to do buying and selling easily and safely. With this e-marketplace, buying and selling in-game currency transactions will be easier, faster, and also scam-free.